Effects of doping concentration on structural, morphological, optical and electrical properties of tungsten doped V2O5 nanorods. Issue 6 (15th April 2018) - Pradeep, I.; Ranjith Kumar, E.; Suriyanarayanan, N.; Srinivas, Ch.; Mehar, M.V.K.
Abstract: Pure and tungsten-doped V2 O5 (Wx V2 O5 ; x = 5%, 10% and 15%) nanorods were produced by the wet chemical method followed by annealing at 60 °C for 12 h and 600 °C for 1 h. The influence of dopant concentration on the structural, morphological, optical and electrical properties of V2 O5 nanorods were investigated through XRD, SEM-EDS, TEM, PL and DC conductivity studies. XRD pattern analysis reveals that the pure and tungsten doped samples are annealed at 60 °C exhibits anorthic phase and annealed at 600 °C, the anorthic is phase disappeared and emerged as an orthorhombic phase. Also, structural analysis shows that the Wx V2 O5 (x = 15%) lattice is found to be secondary phase. The gradual morphological transformation of nanostructures due to the incorporation of tungsten is depicted through SEM/TEM characterizations. The relative differential structure of tungsten-doped V2 O5 nanorods is promptly registered by SEM analysis. EDS result confirms the presence of tungsten and also oxygen vacancies in doped V2 O5 . The PL quenching was observed with doping is due to the absorption of energy from the defect emission in the V 5+ lattice by W 6+ ions. DC conductivity of Wx V2 O5 with respect to different temperatures is explained by the presence of defects. Further, the colloidal form of pure and n-Wx V2 O5 is used to deposit on p-Si substrate for formation of p-n junction by the nebulizer spray technique and the properties of fabricated diodes are investigated under dark and illumination conditions. Also, the Norde's method is used to evaluate the series resistance and barrier height of the Schottky contact. Further, the transient photocurrent measurements were carried out to analyze the photoresponse of the developed diodes.